2011
DOI: 10.1029/2011jd015998
|View full text |Cite
|
Sign up to set email alerts
|

Lightning leader stepping, K changes, and other observations near an intracloud flash

Abstract: [1] An intracloud lightning flash in central New Mexico began with the initiation of a negative stepped leader at an altitude of 8.2 km above sea level. As this leader propagated eastward and upward, at 9.1 km above sea level it passed about 200 m to the north of a balloon-borne, electric field-change instrument (Esonde). After the first leader stopped, a second negative stepped leader began near the point of origin of the first leader, but it propagated away from the Esonde. From the changes in the electric v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 36 publications
9
82
1
Order By: Relevance
“…For the bolt‐from‐the‐blue lightning inFigure 12, if the negative charge removal by the impulse charge transfer is uniformly distributed along the leader channel, we compute a line charge density to be about −0.7 mC/m. This value is not particularly large or small compared to previous measurements of charge density of lightning channels ranging from 0.02 to 32 mC/m [ Proctor , 1997; Thomson et al , 1985; Liu and Krehbiel , 1985; Warner et al , 2003; Lu et al , 2011b; Winn et al , 2011]. Therefore, it remains unclear whether and by how much the main negative charge region is discharged through the impulse charge transfer (within 2 ms after the return stroke) in a bolt‐from‐the‐blue stroke.…”
Section: Impulse Charge Transfer With Different Lightning Morphologymentioning
confidence: 68%
“…For the bolt‐from‐the‐blue lightning inFigure 12, if the negative charge removal by the impulse charge transfer is uniformly distributed along the leader channel, we compute a line charge density to be about −0.7 mC/m. This value is not particularly large or small compared to previous measurements of charge density of lightning channels ranging from 0.02 to 32 mC/m [ Proctor , 1997; Thomson et al , 1985; Liu and Krehbiel , 1985; Warner et al , 2003; Lu et al , 2011b; Winn et al , 2011]. Therefore, it remains unclear whether and by how much the main negative charge region is discharged through the impulse charge transfer (within 2 ms after the return stroke) in a bolt‐from‐the‐blue stroke.…”
Section: Impulse Charge Transfer With Different Lightning Morphologymentioning
confidence: 68%
“…Pasko [2014] assumed that the negative end of stepped leaders jumps forward only when the electric field at that end reached a critical value; Pasko [2014] further assumed that the critical field at the negative end was reached by the continuous extension at the positive end of the leader. This model worked quite well to explain data presented in Marshall et al [2013] and Winn et al [2011].…”
Section: 1002/2014jd021553mentioning
confidence: 75%
“…Winn et al . [] used an LMA and both ground‐based and airborne electric field measurement to study K events associated with an intracloud flash and found similar results as Shao et al . [].…”
Section: Results and Analysismentioning
confidence: 99%